2021
DOI: 10.33774/chemrxiv-2021-vlbbj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nuclear Singlet Relaxation by Chemical Exchange

Abstract: The population imbalance between nuclear singlet states and triplet states of strongly coupled spin-1/2 pairs, also known as nuclear singlet order, is well protected against several common relaxation mechanisms. We study the nuclear singlet relaxation of 13C pairs in aqueous solutions of 1,2-13C2 squarate, over a range of pH values. The 13C singlet order is accessed by introducing 18O nuclei in order to break the chemical equivalence. The squarate dianion is in chemical equilibrium with hydrogen-squarate (SqH−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…It has recently been shown that chemical exchange phenomena, such as reversible protonation, can induce singlet relaxation through modulation of isotropic chemical shifts 39 . We do not anticipate a significant contribution from this mechanism in the current study, since the solvent is aprotic.…”
Section: Measurement and Simulation Of 31 P Spin-lattice And Singlet ...mentioning
confidence: 99%
“…It has recently been shown that chemical exchange phenomena, such as reversible protonation, can induce singlet relaxation through modulation of isotropic chemical shifts 39 . We do not anticipate a significant contribution from this mechanism in the current study, since the solvent is aprotic.…”
Section: Measurement and Simulation Of 31 P Spin-lattice And Singlet ...mentioning
confidence: 99%
“…However, long-lived states (LLSs) have lifetimes T LLS that can be substantial longer than T 1 (1)(2)(3). The discovery of LLSs and the invention of methods to excite them have opened new perspectives, in particular for revealing interactions between potential drugs and target proteins (4)(5)(6), for the observation of hyperpolarized metabolites (7)(8)(9)(10), for probing slow chemical exchange (11), for determining rates of slow diffusion (12,13), for storing nuclear hyperpolarization (14)(15)(16)(17), for selecting signals of interest in peptides and proteins (18,19), and for detecting signals of metabolites in magnetic resonance imaging (MRI) (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Isotopic incorporation was confirmed by mass spectrometry to be 96% 18 O4, 96% 18 O3. For NMR experiments, the tetrabasic sodium uPPi was formulated as a 30 mM solution in deuterium oxide plus 10 equivalents of potassium hydroxide, in order to minimize proton exchange, which can accelerate singlet relaxation (11), and minimize interactions with sodium ions in solution, which our results seem to indicate also accelerates relaxation of both longitudinal and spin order (Fig. S1, Supplementary Materials).…”
Section: Methodsmentioning
confidence: 91%
“…We note, however, that many of the experimental conditions used for our relaxation measurements are different from those that would be encountered in a biological system. First, our experiments were performed at a relatively high pD, to limit deuteron exchange, whereas faster exchange at physiological pD values would be expected to reduce the TS and possibly T1 relaxation times (11). In addition, the nature of the counterion played a role in the relaxation measurements, and the longest T1 times were observed with an excess of K + ions relative to the Na + ions from the synthesized uPPi tetrasodium salt.…”
Section: Discussionmentioning
confidence: 99%